ESTETIKA BUNYI DALAM TEKS SIACUONG PADA MASYARAKAT ADAT KAMPAR PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Miftahul Ilmi; Hasnah Faizah AR; Elmustian Rahman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: The tittle of this study is The Sound of Aesthetic in Siacuong Texts of Kampar Custom Community. This study aims to know sound of aesthetic in Siacuong Texts. The method used is descriptive analysis through the approach of community of Kampar custom . The data of this study were taken from a book entittled Siacuong (Sisombou) in Community of Kampar Custom.The findings of this study were: (1) rhythm a) phoetic (a) 26 data of the first phoetic, (b) 17 data of the middle phoetic, (c) 25 data of the last phoetic b) 4 data of the phoetic, (2) 14 data of ephoni, (3) 11 data of cacaphony, (4) 9 data of anaphora, (5) 2 data of ephyphora, (6) 16 data of aliteration, (7) 15 data of assonance, (8) 3 data of onomathope. The most data found were the first phoetic, the fewest data were ephyphora. Eventhough the fewest data were ephyphora, it doesn’t mean that Siacuong text are not full of aesthetic sounds.Keyword: Sound of Aesthetic, Siacuong texts, Kampar custom comunity